(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In India 70 of the general population economy clearly or by suggestion depending on the agricultural association.which can be 15 - 20% of offers in the hard and fast Indian economy. it’s a huge neighborhood a Green Nation India. in view of the shortfall of preparation and old advancement consistently a considerable number of farmers doing implosion in light of less productivity. Our Project’s standard way to grow the productivity of the best piece of the general population to evolute the rural country into a made country.to make this dream of made country we need to examine to the cultivating territory for present-day propels. one of them we are finding the in all cases free structure to measure the soi supplements are N (Nitrogen), P (Phosphorus), K (Potassium) and show with their thought for farmers at their own lingos like Englis, Hindi, Marathi ( Regional Language Support) to better transparency of an enormous bit of the clueless social classes. with the help of this endeavor, we need to change the circumstance of developing in India. for this, we are developing the system from the above feature with its own power supply necessities fulfilled by Solar Energy and advanced lithium-molecule battery pack. we are developing the system in what course the soil testing technique is at present done in the exploration place by an answer/substance-based testing whose important 6 - 10 Hours of time are cleared out and our farmers can test its earth at its own site two or three minutes. while developing this system we are thing about to95% of accuracy over the lab